Empirical study on ICT use and business strategy for innovation among Japanese SMEs - Hiroki Idota; Teruyuki Bunno; Masatsugu Tsuji (International Telecommunications Society (ITS), 2012)
ICT is expected to play an important role for innovations in Japanese SMEs. In this paper, how ICT use promotes innovation is clarified. In addition, what kind of business strategy SMEs should follow is attempted to achieve innovation by focusing on the behavior of the top management as well as employees. A mail survey was conducted in February 2012 to innovative SMEs. An ICT advancement index is constructed based on the sales management system, groupware, internal SNS and SCM. Logistic regression analysis is applied for verifying the four hypotheses by using the ICT index. The results obtained reveals that SNEs that used ICT for new product development such as collecting customers' needs achieve more product as well as process innovation. And it is confirmed that SMEs which positively share information using ICT achieve more process innovation. And top management should demonstrate the leadership, and manage the product innovation process through top-down including the promotion of ICT use. On the other hand, not only the manager but also the employees have to act flexibly and autonomously to share information by ICT are important in the process innovation that is required to restructure existing business processes.
Keywords: 330